A Study on Customer Satisfaction on Commercial Banks in Theni District - Pooranam, G.; Nandhini, K. (International Research Journal of Management, IT & Social Sciences, 2018)
Banks play a very important role in the economic development of every modern state and country. Banks operate at the heart of the modern economy. Todayâs Business is continually looking for ways to achieve a competitive advantage. Banks essentially are a social organization which rendering financial services to subserve socio-economic objective of the society. Banking system occupies an important place in nationâs economy. In this study, find out the customer satisfaction level of the Commercial banks in Theni District.